INKONSISTENSI PEMANFAATAN RUANG PADA SEMPADAN SUNGAI KOTA PADANG - Rembrandt; Mulia, Fajar Agung; Frinaldi, Aldri; Lanin, Dasman (Jurnal Rekayasa Teknik Sipil dan Lingkungan - CENTECH, 2024)
River borders are natural areas that need to maintain their primary function but currently tend to change into artificial areas, which are used for human activities and building construction. Limited urban land and economic factors are likely the causes of people building in river border areas. This study aims to analyze the function of buildings that are not by the use of space on river borders so that they can be used as a reference for controlling spatial planning. Building and river data are needed to assess the level of consistency and inconsistency of buildings in river border areas. The level of inconsistency is calculated based on the number of buildings located in the river border area divided by the number of buildings outside the river border. The results of the building consistency index analysis of 0.87 indicate that the majority of buildings in Padang City tend to be outside the river border area. However, there are still many buildings that are inconsistent with land use regulations, namely those located in river border areas. The Sungai Pisang watershed is recorded as the most erratic, even though it has the fewest buildings. On the other hand, although the Batang Arau watershed has the largest number of buildings, it shows a lower inconsistency value than the Sungai Pisang watershed and Air Timbulun watershed.